Comparative assessment of head deposition, exhaust gas temperature and sound emission in CI engine using blend fuel - Faheem Ahmed Solangi,; Liaquat Ali Memon,; Saleem Raza Samo,; Muhammad Ramzan Luhur,; Imadad Ali Memona,; Ali Murtaza Ansari,; Sanaullah Mastoi, (Penerbit Universiti Kebangsaan Malaysia, 2024)
Energy has a significant role in the socio-economic growth for any country. The energy originates from fossil fuels, which are non-renewable and enact an undesirable impact on the environment. Waste cooking oil can be utilized in diesel engine directly. Preheating and trans-esterification process are expensive to convert waste cooking oil into biodiesel. This research aims to replace diesel with waste cooking oil as binary blend and compared with diesel fuel. Engine testing at the constant speed of 1300 rpm at constant load. This study revealed that, addition of waste cooking oil reduced exhaust gas temperature as compared to base line fuel. In case of noise emission, sound level for emulsion fuel DF95WCO5 was reduced compared to DF. In this study, a single-cylinder CI engine was run for 200 hours on two fuel samples: DF (diesel fuel) as the baseline fuel and DF95WCO5 (5% waste cooking oil and 95% DF). During the endurance test, the effects of DF95WCO5 on engine head deposits were studied. According to the investigation’s findings, visual inspection of both fuel samples revealed some deposit buildup on injectors. SEM (scanning electron microscopy) and EDX (energy dispersive X-ray spectroscopy) analysis revealed that the engine running with DF95WCO5 formed more carbon deposits on and around the head. It can be concluded that binary emulsion can be used in compression ignition engine without any engine alterations. Consequently, WCO can be proficiently used to reduce detrimental effects and reduce fossil fuel dependency.